Diastereoselective synthesis of tetrahydropyrrolo[1, 2-d]oxadiazoles from functionalized Δ1-pyrrolines and in situ generated nitrile oxides. Issue 8 (31st January 2023) - Ivanova, Evgeniya E.; Shabalin, Dmitrii A.; Ushakov, Igor' A.; Vashchenko, Alexander V.; Schmidt, Elena Yu.; Trofimov, Boris A.
Abstract : A simple method to access tetrahydropyrrolo[1, 2- d ]oxadiazoles in a diastereoselective manner starting from available pyrrolines and in situ generated nitrile oxides was developed. Abstract : Tetrahydropyrrolo[1, 2- d ]oxadiazoles have been synthesized in good-to-excellent yields via the cycloaddition of nitrile oxides ( in situ generated from aldoximes) to readily accessible functionalized Δ 1 -pyrrolines. The reaction proceeds smoothly at room temperature in a two-phase system in the presence of sodium hypochloride as an oxidant to diastereoselectively afford pharmaceutically prospective 1, 2, 4-oxadiazolines fused with a five-membered ring. The reaction tolerates a broad range of substrates, including those with oxidant-sensitive functional groups and competitive reaction sites.